Relative age effect in european professional football. Analysis by position - Salinero, J. J.; Pérez, B.; Burillo, P.; Lesma, M. L. (Journal of Human Sport & Exercise, 2013)
The relative age effect (RAE) in sport consists in the lower presence of athletes born in the months furthest from the cut off date established by the competitive system, which normally coincides with the last months of the year. The purpose of this study is to assess if there is an RAE in European professional football, where the current cut off age for training in the different categories is based on the calendar year; and its analysis by position on the playing field. The analysis has included all the footballers playing in the league championships in the United Kingdom, Italy, Germany, France and Spain (N= 2763). The results of our study confirm an RAE in professional football in Italy, France and Spain. When differentiated by playing position there is a different RAE incidence in the five championships analyzed.